Evaluation of Telemedicine Access with Health Insurance: A Systematic Review - Erlisa Irawati Putri; Diah Ayu Puspandari; Anna Wahyuni Widayanti (Jurnal FARMASIMED (JFM), 2026)
Introduction: Telemedicine transforms healthcare through electronic Communication technologies and offers high-quality medical treatments from a distance. The COVID-19 pandemic is accelerating the adoption of telemedicine, making its integration with insurance financing a strategic step to increase access to healthcare, reduce the financial strain on patients, and ensure continuity of service. Some nations have extended the coverage of private insurance companies and health insurance programs like Medicare and Medicaid to include telemedicine services. Objectives: Assess the impact of implementing telemedicine technology in the context of insurance financing and formulate policy recommendations to improve the accessibility and effectiveness of health services. Methods: Following PRISMA guidelines, a comprehensive search was conducted in Scopus, ScienceDirect, and PubMed, covering studies from 2015 to 2024. The inclusion criteria described telemedicine or telehealth financed by health insurance written in English. Based on the inclusion criteria, seven articles were reviewed in this article. We then assessed the studies’ quality using different research evaluation tools based on the research methods. Results: Health insurance-backed telemedicine has been shown to increase access to healthcare, lessen individuals’ financial burdens, and enhance the standard of medical care. However, several issues, including inadequate infrastructure, low digital literacy, and unclear regulations, continue to impede the use of telemedicine in conjunction with health insurance programs. Adapting to telemedicine presents challenges for elderly populations and people with physical disabilities. Policies, training for healthcare professionals, and technical advancements are required for these services to be inclusive and sustainable. Conclusion: Health insurance-backed telemedicine can improve access and efficiency of care and reduce patients’ financial burdens. By implementing corrective measures, as some countries have successfully done, health systems can maximise the benefits of telemedicine and create more inclusive, efficient, and sustainable health services.